Associations Between Marker Gene Alleles and Doe Traits in Nubian (Zaraibi) Goats in Egypt - Marai, F M; Fandoud, E i Abou; Daader, A H; Ela, A A Abu (Annals of Arid Zone, 2016)
Plasma proteins of Nubian goat does' blood were examined for biochemicalpolymorphism of Immunoglobulin M (IgM), Immunoglobulin G (IgG), ImmunoglobulinP (lgP), Albumin (A), I-Antitrypsin (AnLT), Carbonic Anhydrase Erythrocytes(C.An.Er), Trypsinogen Pancreas (T.P) and Trypsin Inhibitor (Tr.I) by usingone-dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis(SDS-PAGE), with high molecular weight protein standards as reference bands.Analysis of the results revealed the existence of association bet';,ieen reproductivetraits of homozygous Nubian doe genotypes and marker gene alleles. The lowestvalues of age at first kidding was associated with the allele Cb of C.An.Er markergene, abortion in does with the allele pC of IgP and mortality rate with the allelepb of IgP The results also showed that the highest values of each of litter sizeand litter weight at birth and at weaning were associated with the allele Ia ofTr.1 marker gene and those of kilograms of kids produced/life time of doe atbirth and at weaning (the latter parameter, i.e., kilograms of kids produced/lifetime of doe at weaning shows the final output of the traits: prolificacy, milk yieldand pre-weaning mortality) with the allele Aa of A marker gene, Effects of thementioned marker genes on the studied traits were found to be, in general. significant(P